2002
DOI: 10.1124/mol.62.5.1238
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Locations of Distinct Steroid and Vinca Alkaloid Interaction Domains within the Murine mdr1b P-Glycoprotein

Abstract: P-glycoproteins (P-gp) cause the efflux of a wide variety of unrelated hydrophobic compounds out of cells. However, the locations of the sites at which different classes of molecules initially interact with the protein are not well defined. A unique system was developed to search for P-gp drug-interaction domains using mutational analysis. The strategy is based upon identifying mutations that cause a decrease in the activity of P-gp inhibitors, which are structurally related to chemotherapeutic drugs transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…33 Mutations in an eight amino-acid segment of murine IC2 238-245 (239-246 in human P-gp) have been shown to cause reduction in the resistance to vincristine and paclitaxel and to have no influence on daunorubicin and colchicines. [34,35] Hana et al [36] mutated a number of residues in TM11 of P-gp by alanine and found that the mutation in positions G935 and I936 (G939, I940 in human P-gp) displayed an overall decrease in resistance to actinomycin, doxorubicin, vinblastine, and colchicine. These amino acids have not been found in the pocket, however, close to them F938 has been identified.…”
Section: Analysis Of the Binding Regions And Cavity Pocketmentioning
confidence: 98%
See 1 more Smart Citation
“…33 Mutations in an eight amino-acid segment of murine IC2 238-245 (239-246 in human P-gp) have been shown to cause reduction in the resistance to vincristine and paclitaxel and to have no influence on daunorubicin and colchicines. [34,35] Hana et al [36] mutated a number of residues in TM11 of P-gp by alanine and found that the mutation in positions G935 and I936 (G939, I940 in human P-gp) displayed an overall decrease in resistance to actinomycin, doxorubicin, vinblastine, and colchicine. These amino acids have not been found in the pocket, however, close to them F938 has been identified.…”
Section: Analysis Of the Binding Regions And Cavity Pocketmentioning
confidence: 98%
“…[39] Mutations of murine W231, A301, S308 in TM4 and TM5 (human W232, A302, S309, Table 7) influence the resistance profile of the P-gp mutants in relation to steroids and are distinct from those related to Vinca alkaloids (human F239, K242, and A246 binding region 1) located within the cytoplasmic portion of the protein. [34] Figure 8 shows binding region 2 as generated by Site Finder. The front views from the membrane (Figure 8 A), the pore (Figure 8 B), and the top view from outside the cell (Figure 8 C) clearly show that the region is composed of pockets that face the membrane (identified by the gray spheres representing hydrophobic atoms) as well as the pore (identified by the red spheres representing hydrophilic atoms).…”
Section: Analysis Of the Binding Regions And Cavity Pocketmentioning
confidence: 99%
“…Considerable effort has been invested in characterizing drug resistance changes caused by Pglycoprotein mutations [52,53,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. P-glycoprotein mutations that have appeared in cultured cells selected for resistance to particular drugs [130][131][132], and mutations incorporated by site-directed mutagenesis have been evaluated [52,53,127,129,[134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: B Analysis Of Mutations Affecting the Drug Binding Sites Ofmentioning
confidence: 99%
“…P-glycoprotein mutations that have appeared in cultured cells selected for resistance to particular drugs [130][131][132], and mutations incorporated by site-directed mutagenesis have been evaluated [52,53,127,129,[134][135][136][137][138][139][140][141][142][143][144][145]. In many instances, as a result of a particular mutation, resistance to one drug may increase, while the resistance to other drugs may either remain the same or change.…”
Section: B Analysis Of Mutations Affecting the Drug Binding Sites Ofmentioning
confidence: 99%
See 1 more Smart Citation